Coupling of both a transactivation module and a double-stranded DNA-binding domain boosts Cas12i3 variant-based cytosine and adenine editing in plants - Zhang, Chen; Li, Jingying; Li, Yucai; Yan, Lei; Yong, Christina Seok Yien; Li, Shaoya; He, Yubing; Xia, Lanqin (John Wiley and Sons, 2026)
CRISPR/Cas12i3 belongs to the type V-I Cas system, characterized by its smaller protein size and less restricted canonical “TTN” protospacer adjacent motif. Developments of Cas12i3-mediated base editing systems for either C-to-T or A-to-G transitions will expand the editing scope and enrich the plant base editing toolkits for crop improvement. However, while the Cas12i3-based cytosine base editor (CBE) only shows very low editing efficiency in plants, its adenine base editor (ABE) has not been documented as yet. Here, we engineered a series of Cas12i3 (5M)-based CBEs (V0–V5) and ABEs (V0–V5) by fusing a deactivated dCas12i3 (5M) with a transactivation module VP64, a single-stranded DNA-binding domain Rad51, or a double-stranded DNA-binding domain HMG-D, or in combinations, and systemically evaluated their performance in rice protoplasts. Our results demonstrated that synergistic combinations of both VP64 and HMG-D outperformed other architectures and significantly boosted the efficiencies of Cas12i3 (5M)-based CBE and ABE for C-to-T and A-to-G base editing and expanded the editing window. In stable lines, in comparison to the non-fusion control, the optimized Cas12i3 (5M)-based CBE-V5 and ABE-V5 enabled up to 4.78- and 3.35-fold higher editing efficiencies, with the maximum C-to-T and A-to-G efficiencies reaching 32.35% and 38.24%, respectively, and a higher proportion of homozygous mutants in the T0 generation. Furthermore, we generated herbicide-resistant rice germplasm by using CBE-V5 and ABE-V5, demonstrating their potential for precision breeding in crops. Together, here, we report novel Cas12i3 (5M)-based CBE and ABE that substantially enrich base editing toolkits for improvement of rice and potentially other crops.